2023
DOI: 10.3389/fimmu.2022.1062479
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA-seq reveals cellular heterogeneity from deep fascia in patients with acute compartment syndrome

Abstract: IntroductionHigh stress in the compartment surrounded by the deep fascia can cause acute compartment syndrome (ACS) that may result in necrosis of the limbs. The study aims to investigate the cellular heterogeneity of the deep fascia in ACS patients by single-cell RNA sequencing (scRNA-seq).MethodsWe collected deep fascia samples from patients with ACS (high-stress group, HG, n=3) and patients receiving thigh amputation due to osteosarcoma (normal-stress group, NG, n=3). We utilized ultrasound and scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 99 publications
(93 reference statements)
1
2
0
Order By: Relevance
“…However, the relationship between CCL23 and ACS remains obscure. We only found that the level of CCL23 was significantly higher in the AG than in the FG, which was partially consistent with our previous conclusions that there was a significant variation in monocytes and macrophages in patients with ACS (19). Furthermore, we identified 35.75 pg/ml as the cutoff value of CCL23 for predicting ACS in tibial fracture patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the relationship between CCL23 and ACS remains obscure. We only found that the level of CCL23 was significantly higher in the AG than in the FG, which was partially consistent with our previous conclusions that there was a significant variation in monocytes and macrophages in patients with ACS (19). Furthermore, we identified 35.75 pg/ml as the cutoff value of CCL23 for predicting ACS in tibial fracture patients.…”
Section: Discussionsupporting
confidence: 91%
“…IL6 contributes to the regulation of macrophages toward M1 macrophage polarization, whereas CSF-1 and HGF stimulate macrophages toward M2 macrophage polarization. Our previous single-cell RNA analysis showed that the proportion of macrophages has undergone significant changes, especially M1 macrophages and M2 macrophages, indicating that the balance of M1 macrophages and M2 macrophages may affect the development of ACS (19). We can assume that CSF-1, IL6, and HGF are involved in the development of ACS patients.…”
Section: Discussionmentioning
confidence: 95%
“…In our previous study, we found that collagen fibers in the deep fascia were broken in the early stage of ACS, which may be a result of the deep fascia self-regulation and the release of intracompartmental pressure [ 37 ]. In the present study, we found further that the expression of PXDN (promoting the function of fibroblasts [ 38 ]) and CD74 (enhancing the proliferation process of fibroblasts [ 39 ]) were increased in the deep fascia tissue of patients with blister ( p all <0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies at the molecular level have identified some differences in immune cells in ACS patients. In the CD4 cell group, the GZMK+IFN-act subtype and high expression of genes responsible for the production of interferon and heat shock proteins were found [34]. This gives hope for the discovery of targeted cell-based treatments for ACS in the future.…”
Section: Table 1 Most Frequent Causes Of Acs [6]mentioning
confidence: 95%